Efficacy and safety of dietary polyphenol supplementation in the treatment of non-alcoholic fatty liver disease: A systematic review and meta-analysis - Yang, Kailin; Chen, Junpeng; Zhang, Tianqing; Yuan, Xiao; Ge, Anqi; Wang, Shanshan; Xu, Hao; Zeng, Liuting; Ge, Jinwen (Frontiers in Immunology, 2022)
Background: Dietary polyphenols in the treatment of non-alcoholic fatty liver disease (NAFLD) is a novel direction, and the existing clinical studies have little effective evidence for its therapeutic effect, and some studies have inconsistent results. The effectiveness of dietary polyphenols in the treatment of NAFLD is still controversial. The aim of this study was to evaluate the therapeutic efficacy of oral dietary polyphenols in patients with NAFLD. Methods: The Chinese and English literatures published before April 30, 2022 in PubMed, Cochrane, Medline, CNKI and other databases on the treatment of NAFLD with dietary polyphenols were searched. Manual screening, quality assessment and data extraction of search results were conducted strictly according to the inclusion and exclusion criteria. RevMan 5.3 software was used to perform the meta-analysis. Results: The RCTs included in this study involve 8 dietary polyphenol supplementation (Curcumin, Resveratrol, Naringenin, anthocyanin, Hesperidin, Catechin, Silymarin and Genistein) and 2173 participants. This systematic review and meta-analysis found that (1) curcumin may decrease BMI, AST, ALT, TG, TC and HOMA-IR compared to placebo; and curcumin does not increase the occurrence of adverse events. (2) Although the meta-results of all RCTs did not reveal significant positive changes, individual RCTs showed meaningful results. (3) Naringenin significantly decreased the percentage of NAFLD grade, TG, TC and LDL-C, and increased HDL-C, but had no significant effect on AST and ALT; and it is a safe supplementation. (4) Only one team presents a protocol about Anthocyanin (from Cornus mas L. fruit extract) in the treatment of NAFLD. (5) Hesperidin may decrease BMI, AST, ALT, TG, TC, HOMA-IR and so on. (6) Catechin may decrease BMI, HOMA-IR and TG level, and it was well tolerated by the patients. (7) Silymarin was effective in improving ALT and AST and reducing hepatic fat accumulation and liver stiffness in NAFLD patients Conclusion: Based on current evidence, curcumin can reduce BMI, TG, TC, liver enzymes, and insulin resistance; catechin can reduce BMI, insulin resistance, and TG effectively; silymarin can reduce liver enzymes. For resveratrol, Naringenin, Anthocyanin, Hesperidin, Catechin, more RCTs are needed to further evaluate their efficacy and safety.